Factors associated with failed epidural blood patch after accidental dural puncture in obstetrics: a prospective, multicentre, international cohort study. (November 2022) - Gupta, Anil; Van de Velde, Marc; Magnuson, Anders; von Heymann, Christian; Guasch, Emilia; Alahuhta, Seppo; Mercier, Frédéric J.; Schyns-van den Berg, Alexandra M.J.V.; ,
Abstract: Background: Epidural blood patch is commonly used for management of post-dural puncture headache after accidental dural puncture. The primary aim was to determine factors associated with failed epidural blood patch. Methods: In this prospective, multicentre, international cohort study, parturients ≥18 yr receiving an epidural blood patch for treatment of post-dural puncture headache were included. Failed epidural blood patch was defined as headache intensity numeric rating scale (NRS) score ≥7 in the upright position at 4, 24, or 48 h, or the need for a second epidural blood patch, and complete success by NRS=0 at 0–48 h after epidural blood patch. All others were considered partial success. Multinominal logistic regression was used for statistical analyses with P <0.01 considered statistically significant. Results: In all, 643 women received an epidural blood patch. Complete data to classify failure were available in 591 (91.9%) women. Failed epidural blood patch occurred in 167 (28.3%) patients; 195 (33.0%) were completely successful and 229 (38.7%) partially successful. A total of 126 women (19.8%) received a second epidural blood patch. A statistically significant association with failure was observed in patients with a history of migraine, when the accidental dural puncture occurred between lumbar levels L1/L3 compared with L3/L5 and when epidural blood patch was performed <48 h compared with ≥48 h after accidental dural puncture. In patients having radiological investigations, three intracranial bleeds were diagnosed. Conclusions: Failed epidural blood patch occurred in 28.3% of women. Independent modifiable factors associated with failure were higher lumbar level of accidental dural puncture and short interval between accidental dural puncture and epidural blood patch. A history of migraine was associated with a higher risk of second epidural blood patch. Clinical trial registration: NCT02362828.